Predictive Value of Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio in Patients with Coronary Slow Flow - Çetin, Mustafa (Acta Cardiol Sin, 2016)
BACKGROUND: Increased microvascular resistance due to chronic inflammation is assumed to be one of the mechanisms associated with coronary slow flow (CSF). Previous studies have shown that the platelet-to-lymphocyte ratio (PLR) and the neutrophil-lymphocyte ratio (NLR) are markers of inflammation for various diseases. In this study we aimed to evaluate the relationship between CSF and PLR-NLR. METHODS: Seventy-eight patients with CSF and 50 patients with normal coronary flow were enrolled into this study. The study subjects underwent medical examination and testing, after which their platelet-to-lymphocyte ratios and NLR values were calculated. An independent observer measured the coronary flow rate by Thrombolysis in Myocardial Infarction Frame Count (TFC) method. The platelet-to-lymphocyte ratio and NLR values were compared between the groups and correlation analysis was performed to explore the relationship between mean TFC with PLR and NLR. RESULTS: Platelet-to-lymphocyte ratio and NLR values were significantly higher in patients with CSF (p < 0.001). There was a positive significant correlation between TFC with NLR and PLR (Spearman’s Rho: 0.59, p < 0.001 and Spearman’s Rho: 0.30, p = 0.001, respectively). Multivariate logistic regression analysis revealed that NLR is the one independent predictor for CSF. CONCLUSIONS: This study demonstrated an association between CSF and PLR-NLR. Although the exact mechanism could not be explained, our findings support the possible role of inflammation in CSF physiopathology.